2021
DOI: 10.1039/d1dt02658e
|View full text |Cite
|
Sign up to set email alerts
|

N-Donor stabilized tin(ii) cations as efficient ROP catalysts for the synthesis of linear and star-shaped PLAsviathe activated monomer mechanism

Abstract: α-iminopyridine ligands L1 (2-(CH=N(C6H2-2,4,6-Ph3))C5H4N), L2 (2-(CH=N(C6H2-2,4,6-tBu3))C5H4N) and L3 (1,2-(C5H4N-2-CH=N)2CH2CH2) differing by the steric demand of the substituent on the imine CH=N group and by a number of donating nitrogen atoms...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 87 publications
2
13
0
Order By: Relevance
“…While the signals ranging from −523.2 to −469.0 ppm were assigned to the [ L 1–6 SnCl] + cations, the signals ranging between δ = −101.1 and −57.7 ppm correspond to the related [SnCl 3 ] − anions. 8–15 The chemical shifts of the [ L 1–6 SnCl] + cations are in accordance with those of related bis(imino)pyridine-stabilized chlorostannyliumylidenes (range of −482.4 to −411.7 ppm), containing tetra-coordinated tin centers. 7,9 This clearly indicates the coordination of both nitrogen and also oxygen donor atoms in solutions of 1–6 .…”
Section: Resultssupporting
confidence: 64%
See 3 more Smart Citations
“…While the signals ranging from −523.2 to −469.0 ppm were assigned to the [ L 1–6 SnCl] + cations, the signals ranging between δ = −101.1 and −57.7 ppm correspond to the related [SnCl 3 ] − anions. 8–15 The chemical shifts of the [ L 1–6 SnCl] + cations are in accordance with those of related bis(imino)pyridine-stabilized chlorostannyliumylidenes (range of −482.4 to −411.7 ppm), containing tetra-coordinated tin centers. 7,9 This clearly indicates the coordination of both nitrogen and also oxygen donor atoms in solutions of 1–6 .…”
Section: Resultssupporting
confidence: 64%
“…Roesky et al observed a Lewis base mediated ionization of SnCl 2 and reported the synthesis of [(DIMPY)SnCl] + [SnCl 3 ] − , where DIMPY is 2,6-[(Me)CN(C 6 H 3 -2,6-iPr 2 )] 2 C 5 H 3 N. 7 This approach has become universal for obtaining a wide range of tin( ii ) cations with a general formula [D → SnX] + (D = Lewis base, X = halide or pseudohalide) (Chart 1, A–G ). 8–15…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, a recent publication of Novák et al discussing the usefulness of the cationic Sn(II) complexes (Schemes 26-28) as catalysts for ROPs of LLA should be mentioned. 160 In the title and in the section "Discussion" those authors claim that these cationic catalysts initiate an activated monomer mechanism. However, MALDI TOF mass spectra and NMR spectroscopic end group analyses were missing.…”
Section: Polymer Chemistry Reviewmentioning
confidence: 99%